Risk factors associated with type 2 diabetes mellitus in early adulthood within urban populations - Eliza Fitria; Ermi Girsang; Ali Napiah Nasution (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Type 2 diabetes mellitus (DM) is a chronic metabolic disease whose prevalence is increasing globally, including in Indonesia. Risk factors such as unhealthy diet, low physical activity, smoking, low fiber consumption, and pesticide exposure contribute significantly to the incidence of type 2 DM. Purpose: To analyze the association between pesticide exposure, smoking habit, physical activity, consumption of sweet foods, and fiber consumption with the incidence of type 2 DM in the early adult population. Method: A cross-sectional design was conducted to 110 early adult respondents aged 24-40 years. Data were collected through a structured questionnaire and analyzed using the chi-square test with a significance level of 5%. Odds Ratio (OR) was used to assess the odds of risk. Results: Pesticide exposure (p=0.009; OR=3.4), low physical activity (p=0.004; OR=3.5), excessive consumption of high-sugar foods (p=0.009; OR=3.1), and low fiber consumption (p=0.004; OR=3.7) were significantly associated with the incidence of type 2 DM. However, smoking habit showed no significant association (p=0.453). Conclusion: Factors such as pesticide exposure, low physical activity, excessive consumption of sugary foods, and low fiber consumption are significant predictors of type 2 DM. Healthy lifestyle education and control of environmental risk factors are recommended to reduce the prevalence of type 2 DM.